El surgimiento y diversificación de las derechas de Argentina y Uruguay en la primera mitad del siglo XX - Olga Echeverría (Nuevo mundo - Mundos Nuevos, 2017)
With a common past, by the end of 19th century and beginning of 20th, Argentina and Uruguay entered Capitalism by exporting raw materials and importing european manufactured goods. In a political dimension, both countries faced consolidation of National States that had to overcome harsh political struggles from previous period. In spite of being in a process of modernization, the two countries took relatively dissimilar roads which involved the conformation of different political systems in terms of praxis and values. As a response, in those different contexts, plural political and ideological trends arise which, in varying degrees, demurred democracy, worker demonstrations, left-wing ideas, social mobility and the destruction of hierarchies which were thought as if they were “natural”. As in other aspects the right-wings of first half of 20th century in both countries, considering contrasts in political systems, have similar features and strategies along with different projects, influences and perspectives. Some aspects derived of internationalization of disputes and the impact of totalitarian regimes allowed confluences and contacts that had never been so notorious and public, but at the same time evinced disagreements and tensions.